Black Lives Matter as "social movement": theorizing the materiality of movement of the social - Clark, Jordin, author; Dunn, Thomas, advisor; Dickinson, Greg, committee member; Cespedes, Karina, committee member (Colorado State University. Libraries, 2017)
Utilizing Michael Calvin McGee's notion of social movement as a set of meanings that move the social, this thesis builds upon and adjusts the discursive focus of McGee's rhetorical theory of social movement to include materiality, particularly material movement as influential in changing the social. To do so, I build upon theories of sociality, space, and movement to present movement and motion as material texts that hold rhetorical power to inflect and produce our cultural and social understandings of our sociality. Analyzing the Black Lives Matter's Black Friday protest at the Magnificent Mile in Chicago in 2015, this thesis argues that protests—in their material movements—remake public spaces and the societal, spatial, and individual social body to carve out an imaginary and thus sociality in which Black lives matter. The aptly named Black Lives Matter movement is a social movement that makes visible systemic racism that disciplines, endangers, and marginalizes Black lives, with the goal to reimagine a world where Black people are free to exist and live—where Black lives matter. Our current social and spatial imaginary constructs the Black body as a subject of exclusion and allows whiteness to ignore and disregard that Black lives matter. However, during the Black Friday protest at the Magnificent Mile in Chicago in 2015, as this thesis argues, the protesters disrupted the embodied and spatial rhythms of the Magnificent Mile to open a fissure within the shopper's social/spatial imaginary wherein the protesters compelled them to recognize Black lives while urging them to accede that they matter.
Keywords: materiality; movement; rhetoric; McGee; Black Lives Matter; protest